Education in conflict: how Islamic State established its curriculum. Issue 4 (3rd July 2020) - Arvisais, Olivier; Guidère, Mathieu
ABSTRACT: In places where Islamic State (ISIS) took hold in Syria and Iraq between 2014 and 2017, its domination was followed by an elaborate educational system. As such, the terrorist organization's 'state program' is a unique case in recent history. Indeed, not only did it overturn the existing education system in Syria and Iraq, resulting in a hiatus in the schooling of children and teens, the organization went a step further by creating its own alternative educational system in its stronghold regions replacing the Syrian and Iraqi formal system. This topical paper presents a case study whose purpose is to produce a description and interpretations through interviews and official document analysis of the way ISIS established its education system. To understand these unique, unprecedented circumstances, we retrace the steps taken by ISIS to institute its education system. Our results show among other things that ISIS acted as a proto-state and attempted to redefine education through the lens of a sectarian vision of Islam. By this study, we hope to shine light on the unique context in which the curriculum was prepared and implemented.